Antenatal and Postnatal Depressive symptoms in Kuwait: results from the TRACER Study - Pampaka, Despina (Cyprus International Institute for Environmental and Public Health, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Introduction: The perinatal period is characterized by hormonal and neurobiological changes which may result in mood changes, making women more susceptible to depression. Prenatal depression and postnatal depression are common in women and have been associated with adverse outcomes of both the child and the mother. Limited evidence exists in the Gulf countries about depression during and after pregnancy, as well as for their correlates. The aims of this PhD dissertation work were: a) to provide an estimate of the prevalence of antenatal depressive symptoms in Kuwait, as an indicator of depression, and identify the risk factors associated with it; b) to examine whether antenatal depressive symptoms and other potential risk factors are associated with adverse perinatal outcomes, such as preterm birth, small for gestational age, and large for gestational age; and c) to estimate the prevalence of postnatal depressive symptoms and identify the risk factors associated with it as well as examine the link with antenatal depressive symptoms. Methods: This was a secondary analysis of data collected from 1938 women who participated in the TRansgenerational Assessment of Children's Environmental Risk (TRACER) Study - a longitudinal prospective birth cohort study in Kuwait. A baseline questionnaire was administered to all participants at enrollment while a stress questionnaire, that also included the Edinburgh Postnatal Depression Scale (EPDS), was administered at a later visit in person or through a phone-interview. A postnatal phone interview was conducted to obtain information about the birth date, birth weight, adverse outcomes during pregnancy, and postnatal depressive symptoms using the EPDS. A score of 10 or greater in the EPDS was used as a cut-off point to determine the presence of depressive symptoms antenatally and postnatally. Chi-square tests, crude and multiple logistic regression models were used to identify the risk factors of antenatal and postnatal depressive symptoms, preterm birth, small and large for gestational age babies and assess their effect. Results: The prevalence of antenatal depressive symptoms was 20.2% (95% CI: 18.4-22.1) while that of postnatal depressive symptoms was 11.7% (95% CI: 10.1-13.5). Antenatal depressive symptoms were reported more by women in the third trimester compared to those in the second trimester, women of lower family income, those who had experienced more than five traumatic events during their lifetime, and those women that had self-reported history of depression prior to pregnancy. Pregnancy-related anxiety, moderate and higher perceived stress, post-traumatic stress disorder symptoms, and fair or poor quality of mental health, as well as poor quality of physical health during pregnancy were also associated with the presence of antenatal depressive symptoms. In our sample, antenatal depressive symptoms did not predict adverse birth outcomes; preterm birth was associated with in vitro fertilization and previous preterm delivery, small for gestational age was associated with lower family income and a female baby, while large for gestational age was associated with a non-Kuwaiti nationality, parity, and a male baby. Antenatal depressive symptoms were the strongest risk factor for developing postnatal depressive symptoms. Other determinants of postnatal depressive symptoms included lower family income, being Kuwaiti, and reporting post-traumatic stress disorder symptoms in pregnancy. In the group of women with no depressive symptoms in pregnancy the mother’s mental well-being and social support from her network were also significant risks factors for postnatal depressive symptoms. Conclusions: Our results showed that in Kuwait, 1 in 5 women experiences depressive symptoms antenatally and 1 in 9 women postnatally. We recommend that antenatal and postnatal depression screening is performed as a routine test, especially among women who are at a higher risk of experiencing depression during the perinatal period. Improving the mental well-being of women during pregnancy, helping them reduce their anxiety related to pregnancy, and making them feel less isolated, could also potentially lower the risk for postnatal depressive symptoms and their sequelae.
Keywords: Perinatal period; Prenatal depression; Antenatal depressive symptoms